Metagenomic Insights into Pathogenic Characterization of ST410 Acinetobacter nosocomialis Prevalent in China - Liang Jing; Zhuofei Xu; Youping Zhang; Dayong Li; Yaqin Song; Hongjie Hu; Yuan Fang; Wei Zhu (Pathogens, 2022)
Acinetobacter nosocomialis is a prevalent opportunistic pathogen that causes hospital-acquired infections. The increasing threats from A. nosocomialis infections have led to attention from the scientific and medical communities. Metagenomic next-generation sequencing (mNGS) was performed for an exudate specimen collected from an ICU patient with wound infection, followed by sepsis, in Tongji Hospital. Three assembly strategies were employed to recover the genome of A. nosocomialis in the metagenomic sample. Together with publicly available genomes of A. nosocomialis, the features of population genetics and molecular epidemiology were deeply analyzed. A draft genome was reconstructed for the metagenomic strain WHM01, derived from the ST410 A. nosocomialis dominating the microbial community, thereby prompting its highly pathogenic risk, which is associated with infection and persistence. The structure of the bacterial pangenome was characterized, including the 1862 core and 11,815 accessory genes present in the 157 strains. The genetic diversity of the genes coding for the 128 virulence factors assigned to 14 functional categories was uncovered in this nosocomial pathogen, such as the lipooligosaccharide, capsule, type IV pilus, and outer membrane proteins. Our work revealed genomic properties of ST410 A. nosocomialis, which is prevalent in China, and further highlighted that metagenomic surveillance may be a prospective application for evaluating the pathogenic characteristics of the nosocomial opportunistic pathogens.